Implementation of AMURT Reading Book Program in an Effort to Instill Early Reading Literacy at Permata Bangsa Islamic Kindergarten Semarang - Lathifa, Aisha Luthfatul; Sumanto, Reni Pawestuti Ambari Sumanto (Universitas Negeri Semarang, 2025)
Literacy is defined as the ability to recognise written symbols and form meaningful sentences. To cultivate public interest in reading, the government has implemented a range of initiatives. One such initiative is the National Literacy Movement. As a non-governmental organisation engaged in social humanitarian work, AMURT participated in this effort by launching the Reading Book Programme to cultivate reading literacy. The present study aims to examine the program's implementation at Permata Bangsa Islamic Kindergarten in Semarang, as well as the factors that support or inhibit early reading literacy. The present study employed a qualitative descriptive method. A data set was collected from the principal, teaching staff, and the student guardians at Permata Bangsa Islamic Kindergarten. The data presented herein were collected through a combination of interviews, observations, and a documentary study. The interactive analysis technique pioneered by Miles and Huberman was utilised for the purposes of data analysis. The findings indicated that the AMURT Reading Book Programme is operationalised at Permata Bangsa Islamic Kindergarten through three activities: the lending of reading books, the utilisation of books as educational resources, and the establishment of reading corners. Supporting factors include various parties' support, strengthened governance, optimal utilization of facilities by the school, and both parties' commitment to maintaining the reading books.